ACUTE PERFORMANCE ON A VESTIBULAR AND OCULAR MOTOR SCREENER AND RECOVERY FOLLOWING CONCUSSION. Issue 3 (31st March 2019) - Burkhart, Scott O.; Ellis, Christine; Smurawa, Troy M.
Background: Concussion injuries are synonymous with vestibular impairments and symptoms include dizziness, impaired balance, and problems with gaze stability (Covassin et al., 2014). Common ocular motor impairments after a concussion include convergence/accommodative insufficiencies and saccadic dysfunction (Mucha et al., 2014). Vestibular and ocular motor impairments have been linked to worse outcomes following concussion (Pearce et al., 2015), including prolonged recovery (Corwin et al., 2015). The purpose of the current study was to determine which VOMS impairments were linked with longer recovery. Methods: Pediatric patients diagnosed with concussion (n = 131) presenting to an outpatient concussion clinic within 7 days from their initial date of injury were administered a standardized version of the VOMS. Patients were administered the VOMS by certified athletic trainers educated and trained on administration. The VOMS consists of nine measures and was validated by the University of Pittsburgh (Mucha et al., 2014) as a symptom provocation measure with a symptom rating of 0-10 with convergence measured in centimeters, and scores of 6 cm or greater being indicative of abnormal. Demographic, acute injury, and baseline values were summarized using descriptive statistics. Point estimates and 95% confidence intervals were calculated for all end points. Results: 131 patients with a mean age of 13.5 + 2.4 completed the VOMS within 7 days (mean = 3.2 + 1.7) of a diagnosed concussion. The sample was evenly divided by gender (52.7% male, 47.3% female). Patients were grouped by recovery time: <14 days (n = 19, 14.5%) 15-28 days (n = 64, 48.9%), and 29-120 days (n = 48, 36.6%). In the <14 day recovery group, 5.2% (n = 2) reported a history of concussion, 15.8% (n = 3) reported a history of migraine, and 5.2% (n = 2) reported a history of psychiatric diagnosis. In the 15-28 day recovery group, 21.9% (n = 14) reported a history of concussion, 9.4% (n = 6) reported a history of migraine, and 6.5% (n = 4) reported a history of psychiatric diagnosis. In the 29-120 day recovery group, 25% (n = 12) reported a history of concussion, 25% (n = 12) reported a history of migraine, and 6.25% (n = 3) reported a history of psychiatric diagnosis. Descriptive statistics for baseline VOMS symptoms were recorded for the <14 day recovery group; headache (mean = 1 + 1.49, CI = 0.7 -1.3), dizziness (mean = 0.2 + 0.5, CI = 0.1-0.3), nausea (mean = 0 + 0, CI = 0-0), and fogginess (mean = 0.9 + 1.5, CI = 0.5 -1.3), for the 15-28 day recovery group; headache (mean = 3.3 + 2.4, CI = 3-3.6), dizziness (mean = 1.5 + 1.9, CI = 1.3 -1.7), nausea (mean = 0.8 + 1.7, CI = 0.6 -1), and fogginess (mean = 1.7 + 2.2, CI = 1.4-2), for the 29-120 day recovery group; headache (mean = 4.4 + 2.2, CI = 4.1-4.7), dizziness (mean = 1.9 + 2.2, CI = 1.6-2.2), nausea (mean = 1.4 + 2.2, CI = 1.1 -1.7), and fogginess (mean = 2.4 + 2.9, CI = 2-2.8). VOMS convergence in centimeters across trials for the <14 day recovery group; T1 (mean = 2.6 + 2.4, CI = 2.1-3.1), T2 (mean = 3.4 + 2.4, CI = 2.9-3.9), and T3 (mean = 3.8 + 2.5, CI = 3.2-4.4), for the 15-29 day recovery group; T1 (mean = 3.9 + 3.9, CI = 3.4-4.4), T2 (mean = 4.8 + 4.2, CI = 4.3-5.3), and T3 (mean = 5.3 + 5.1, CI = 4.7-5.9), for the 29-120 day recovery group; T1 (mean = 6.9 + 5.2, CI = 6.1-7.7), T2 (mean = 8.3 + 1.8, CI = 7.4-9.2), and T3 (mean = 9.6 + 2.1, CI = 8.6-10.6). VOMS symptom provocation increase of +2 and +3 from baseline were totaled for each recovery group. Abnormal convergence greater than 6 cm on any trial was totaled for each group. Percentages for all 3 recovery groups with symptom provocation of +2, +3, and abnormal convergence were calculated. In the <14 day recovery group, 21% had a +2 symptom provocation on at least one symptom, 16% had a +3 symptom increase on at least one symptom, and 16% had abnormal convergence greater than 6 cm on at least one convergence trial. 11% of the <14 day recovery group had a +2, +3, increase and abnormal convergence greater than 6 cm. In the 15-29 day recovery group, 69% had a +2 symptom provocation on at least one symptom, 34% had a +3 symptom increase on at least one symptom, and 38% had abnormal convergence greater than 6 cm on at least one convergence trial. 13% of the 15-29 day recovery group had a +2, +3, increase and abnormal convergence greater than 6 cm. In the 29-120 day recovery group, 85% had a +2 symptom provocation on at least one symptom, 60% had a +3 symptom increase on at least one symptom, and 58% had abnormal convergence greater than 6 cm on at least one convergence trial. 38% of the 29-120 day recovery group had a +2, +3, increase and abnormal convergence greater than 6 cm. Conclusion: The current study identified symptom provocation of +2 and +3 as well as abnormal convergence greater than 6 cm were the most synonymous with recovery across the three recovery groups. Clinicians should consider these findings in providing recommendations and discussing anticipated recovery with patients. Further research is needed to determine more definitive parameters when predicting recovery following concussion.